Structure and conductivity of Nd6MoO12-based potential electron–proton conductors under dry and wet redox conditions. Issue 2 (18th January 2019) - Shlyakhtina, A. V.; Avdeev, M.; Abrantes, J. C. C.; Gomes, E.; Lyskov, N. V.; Kharitonova, E. P.; Kolbanev, I. V.; Shcherbakova, L.G.
Abstract : Based on rhombohedral structure ( R 3̄) complex Nd10 Mo2 O21 compound has proton conductivity ∼8 × 10 −4 S cm −1 at 600 °C. Abstract : Nominal compositions Nd6 MoO12 (3 : 1) and Nd10 Mo2 O21 (5 : 2) were prepared by high-temperature synthesis in air from a mechanically activated mixture of Nd2 O3 and MoO3 . Phase-pure Nd6 MoO12− δ and Nd6 MoO12− α have been obtained at 1600 and 1650 °C, respectively. They are both slightly rhombohedrally distorted derivatives from the cubic fluorite structure. Nd10 Mo2 O21 with a lower content of Nd2 O3 was shown to be a more complex phase based on the rhombohedral phase ( R 3̄) in the 1600–1650 °C temperature range. As a result of the formation of a more complex rhombohedral phase, the conductivity of Nd10 Mo2 O21 changes dramatically in comparison with Nd6 MoO12− δ . In wet air Nd6 MoO12− δ is a p-type electronic conductor, whereas proton conductivity dominates in Nd10 Mo2 O21 over the entire temperature range studied. The electrical conductivity dependence of Nd6 MoO12− δ on the oxygen partial pressure shows a V-type behaviour typical of a transition from a p-type to n-type conductivity mechanism at 800 ≤ T ≤ 1000 °C. There is no p-type conductivity contribution in Nd10 Mo2 O21 in the same temperature range. The prevalence of electronic conductivity in the samples with nominal composition Nd6 MoO12 in a wide temperature range is due to the fact that Nd and Mo in the fluorite materials are readily reduced. Predominantly Nd 3+ and Mo 6+ forms exist in more complex rhombohedral phase Nd10 Mo2 O21 and it has proton conductivity ∼8.5 × 10 −3 S cm −1 at 800 °C. Thus, the loss of dimensional stability is more characteristic of fluorites and rhombohedral phases with small rhombohedral distortion (Nd5.4 Zr0.6 MoO12.3, Nd6 MoO12− δ ) than more complex rhombohedral phases based on ( R 3̄) (Nd10 Mo2 O21 ). A comparative high-temperature in situ neutron diffraction study under high vacuum of rhombohedral Nd6 MoO12− δ and cubic fluorite Nd5.4 Zr0.6 MoO12.3 showed that the former transforms to the high-temperature cubic fluorite type above ∼1140 °C while the latter retains its cubic structure in the studied range up to 1350 °C.